Manufacture and Characterization of Sensors for Optimizing the Detection of Water Contaminated by Sugar Mill Effluents in Waterways Around Sugar Mill - Leksono, Eguh Budi; Hanif, Amar; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
Waste produced by sugar factories will affect the quality of water in the surrounding environment. The manufacture and characterization of sensors to optimize the detection of water contaminated by sugar mill effluents in waterways around sugar mills has been carried out. This study aims to create and characterize resistance sensors as an alternative tool to distinguish water polluted from sugar factory wastewater and clean water from sugar mill waste. The method used in this study is the Arduino UNO-based water resistance sensor method which is carried out in three stages, the first is the preparation of tools and materials, the second is data retrieval, and the third is data processing. This study uses a water resistance sensor, Arduino UNO as a controller, and also equipped with LED indicators. The results showed that the Arduino UNO-based water resistance sensor can be used as a tool to distinguish water contaminated by sugar mill waste and clean water from sugar mill waste.